ANALISIS DAMPAK PEMUTUSAN SUMBER LISTRIK TERHADAP KEGAGALAN SISTEM GENERAL ALARM DALAM PENANGANAN KEBAKARAN SAAT FLOATING REPAIR (STUDI KASUS KM DHARMA KENCANA) - Aditya, Arya Rigar; Oktavera Sulistiana; Nur Indah Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Floating repair is a high-risk maintenance activity that significantly increases the potential for shipboard fires due to hot work operations, electrical equipment usage, and changes in ship operational conditions. One of the common practices during floating repair is the shutdown of the vessel's electrical power system to facilitate maintenance activities. Consequently, electrically operated fire protection systems, including the general alarm and fire detection system, may become unavailable, reducing the effectiveness of emergency communication during fire incidents. This study aims to analyze the impact of electrical shutdown on the failure of the general alarm system during a fire emergency aboard KM Dharma Kencana while undergoing floating repair at PT Adiluhung Sarana Segara Indonesia. A qualitative descriptive approach was employed using direct observation, interviews with ship officers and crew members, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing based on SOLAS requirements, the ISM Code, and shipyard safety guidelines. The findings indicate that electrical shutdown rendered the general alarm, smoke detection system, and fire notification system inoperative. Consequently, emergency information had to be communicated manually through verbal shouting among crew members, resulting in delays in hazard identification, emergency coordination, and initial firefighting response. Although the fire was eventually controlled through collaboration between the ship's crew and shipyard personnel, the incident revealed significant weaknesses in emergency communication during floating repair operations. This study recommends implementing temporary emergency communication systems using portable alarm devices, providing backup power for essential alarm systems, and developing specific standard operating procedures for emergency response during floating repair to improve maritime safety.